2006
DOI: 10.1007/s10464-005-9003-6
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Hmong Refugees' Well‐Being Through Mutual Learning: Valuing Knowledge, Culture, and Experience

Abstract: Refugees who resettle in a new country face numerous struggles, including overcoming past traumas and coping with post-migration stressors, such as lack of meaningful social roles, poverty, discrimination, lack of environmental mastery, and social isolation. Thus, in addition to needing to learn concrete language skills and gain access to resources and employment, it is important for refugees to become a part of settings where their experiences, knowledge, and identity are valued and validated. The Refugee Wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 22 publications
4
58
0
Order By: Relevance
“…This has been done with moderate success by the local RWP through two interventional components, mutual learning and advocacy. The former focuses on the pragmatic and therapeutic elements of cultural exchange (Goodkind 2006), to foster cohesiveness and support within the RWP cohorts themselves, and to serve as fora for the reinforcement and/or generation of new familial roles in response to resettlement stressors. Advocacy provided support in education, as well as health care, finding safe housing, and assisting with immigration and residency logistics (Goodkind et al 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been done with moderate success by the local RWP through two interventional components, mutual learning and advocacy. The former focuses on the pragmatic and therapeutic elements of cultural exchange (Goodkind 2006), to foster cohesiveness and support within the RWP cohorts themselves, and to serve as fora for the reinforcement and/or generation of new familial roles in response to resettlement stressors. Advocacy provided support in education, as well as health care, finding safe housing, and assisting with immigration and residency logistics (Goodkind et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The model was initially developed by community psychologist Dr. Jessica Goodkind, and first implemented among Hmong adult refugees in the state of Michigan (Goodkind 2005, 2006; Goodkind et al 2004). Subsequently, the RWP model was applied in New Mexico with African refugees from 2006–2008 (Goodkind et al 2013; Hess et al 2014), with Iraqi refugees in 2009 from which this data has been collected, and currently with groups comprised of multiple national origins, with the hope of addressing mental health challenges experienced by refugees as a result of war trauma, flight, refugee camp conditions, and difficulties related to resettlement.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also found that the loss of valued social roles impacts the health and well-being of refugees (Goodkind, 2006; Miller, Worthington, Muzurovic, Tipping, & Goldman, 2002). Refugee adults typically experience the loss of multiple social roles.…”
Section: Theoretical Justification and Empirical Support For The Intementioning
confidence: 99%
“…Binney's (1968aBinney's ( , 1968b early work on the social structure of the Hmong (White Meo) found Hmong residence to be patrilocal, with families that are patrilineally related tending to setup homes within close proximity to one another, thus forming localized patrilineage relations. Moreover, the Hmong historically tended to promote collectivist approaches in which clan connections (Scott 1982) and group solidarity (Goodkind 2006) are seen as particularly important. Ranard (2004) hypothesized that because the Hmong have a long turbulent history of conflicts and wars with other ethnic groups, they tend to internalize the idea that survival of the individual is dependent on group survival.…”
Section: The Ties That Bindmentioning
confidence: 99%
“…However, unlike lineage, members of the same clan may not be able to trace themselves back to a common ancestor. Strong clan relations are deemed advantageous because of the support system that such relations foster (Dunnigan 1982;Symonds 2004;Goodkind 2006), even if this advantage comes at a cost of diminished individual freedom. It is generally accepted that there are a total of eighteen clans or xeem: Binney (1968a) suggested that clan could be thought of as a 'maximal' lineage that in theory could be traced back to the clan founder.…”
Section: Clan Relationsmentioning
confidence: 99%